Isolated Terminal Myelocystocele: A Rare Spinal Dysraphism - Mirza, Bilal (EL-MED-Pub, 2011)
Terminal myelocystocele is a rare spinal dysraphism that present as lumbosacral mass. Magnetic resonance imaging (MRI) is the modality of choice for preoperative diagnosis. A 2.5 months old female baby presented with lumbosacral skin covered mass. There were no associated neurological deficits. MRI of the lesion suggested two cysts, one of which was continuous with the central canal of the spinal cord. At operation terminal myelocystocele was found with tethering of the spinal cord. Untethering of the spinal cord and repair of the myelocystocele performed with uneventful recovery.